ULTILIZATION OF SOLID ORGANICS FROM LARVAE Oryctes rhinoceros (Linn.) SCARABAEUS.: KOLARHINO AND LOCAL MICROORGANISMS FROM Luffa acutangula (L.) Roxb. ON THE SUSTAINABILITY OF HISTOSOL SOIL FERTILITY AND HEALTH - Erwin Junaidi Lubis; Sartika Pakpahan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The excrement of horned beetle (Oryctes rhinoceros (Linn.) Scarabeus.) larvae, namely Kolarhino, in the soil of palm oil (Elaeis guineensis Jacq.) plants contains minerals that can and can improve soil fertility and health. These larvae contain minerals that can fertilize the soil, such as zinc (Zn), felium (Fe), potassium (K), and phosphorus (P) which are important for plant growth and soil health. Luffa acutangula (L.) Roxb. plants contain many carbohydrates and sources of nutrients needed by microbes to multiply. The mineral content of gambas in the process of local microorganisms for soil fertility is calcium (Ca), phosphorus (P), and felium (Fe) which are very supportive in the process of soil fertility. In this study, the mixture given to Histosol soil is the content of Oryctes rhinoceros (Linn.) Scarabaeus. larvae faeces: Kolarhino and Local Microorganisms (MoL) of Luffa acutangula (L.) Roxb. gave a positive impact on Histosol soil both physically and chemically.